Environmental changes on the west coast of the Gulf of Thailand during the 8.2 ka event - Akkaneewut Chabangborn (2020)
© 2019 Elsevier Ltd and INQUA The expression of the abrupt cooling of the 8.2 ka event in the tropics is poorly understood. In this study, we applied lithostratigraphy, loss on ignition, grain size and pollen analyses to sedimentary sequences from Thale Noi, which is located in the west coast of the Gulf of Thailand, in order to reconstruct the regional environmental history during the 8.2 ka event. Our results, based on sediment. This characteristics and pollen records, indicated that the study area was likely to have flooded prior to c. 8300 cal. a BP. The fall in sea-level coincided with a high precipitation, inferred from grain size, between c. 8250 and 8100 cal a BP. The increased precipitation can be attributed to the strengthening of the northeast (winter) monsoonal rains in the western Gulf of Thailand. The timing of the sea-level fall and strengthen stronger winter monsoon is consistent with the abrupt decrease in the temperature records emanating from the northern hemisphere. Subsequently, we observed a sea-level rise from c. 8100 to 7950 cal a BP, which potentially continued till c. 7650 cal. a BP. The possibility of coastal erosion was detected by a hiatus in the sedimentary sequences dated between c. 7950 and 7650 cal a BP. Then, a standstill of the sea-level occurred from c. 7650 to 7100 cal a BP. This transgression is suggested to have caused coastal erosion that resulted in a hiatus in the sedimentation process between c. 7950 and 7650 cal a BP. Correspondingly, fluctuations in the monsoon strength resulted in an overall decreased precipitation from c. 8100 to 7450 cal a BP, although punctuated wet intervals were observed at c. 7950 and 7575 cal a BP.